Aryldiazenyl Radicals from Arylazo Sulfones: Visible Light‐Driven Diazenylation of Enol Silyl Ethers. Issue 11 (21st February 2020) - Othman Abdulla, Havall; Scaringi, Simone; Amin, Ahmed A.; Mella, Mariella; Protti, Stefano; Fagnoni, Maurizio
Abstract: A versatile protocol for the diazenylation of enol silyl ethers under visible light irradiation is presented herein. The reaction is based on the underused reaction of a nitrogen‐based radical (the diazenyl radical) with an enol silyl ether. Arylazo sulfones were used as photoactivatable precursors of these diazenyl radicals. The resulting azaderivatives are potentially bioactive compounds as well as starting materials for the synthesis of N ‐containing heterocycles. Abstract :